Inclusive or Exclusive? Analyzing Minority Representation in Tamil Nadu and CBSE Textbooks - Manivannan, T.; Tasnim, M.E. (University of Jaffna, 2025)
Textbooks are the primary knowledge hub or a resource for marginalized children who lack access to commercially produced supplementary materials or any other educational materials available in the mainstream market. These textbooks given in the school play a huge role in shaping their perspectives on culture, identity, and other consciousnesses that build their understanding of society. When textbooks maintain an unbiased and inclusive approach, they foster equitable learning. However, if the textbooks are biased and favour the majority population and neglect the marginalized groups, then, it is devoiding of meaningful relevance of content for these groups. Already, the standardization of languages due to globalization has positioned English as a dominant “killer language”. Likewise, these regional majority languages in various Indian states are taking the same role by subjugating minority languages and dialects. The primary victims, in this process of extinction, are the tribal languages, immigrants’ languages, and dialects. This state is further exacerbated by policies that lie only on paper. To understand whether the textbooks are inclusive, this study critically examines the English textbooks of Tamil Nadu State Board curricula and Central Board of State Education curricula of grades 1- 10. The qualitative content analysis approach is used to evaluate the textbook’s representation in terms of linguistic, cultural, and history of tribal communities. The findings showed significant gaps in representation, particularly in the Tamil Nadu State Board’s primary-level textbooks (grades 1-3), where tribal identities are completely absent. Even though Tamil Nadu is home to indigenous communities such as the Irula, Kurumba, and others, their presence in the curriculum remains very rare. Further doing a comparative analysis between state and central board textbooks, it is found that there is a persistent underrepresentation of tribal communities across both curricula. By ignoring this, we are perpetuating systemic invisibility and cultural homogenization. The study concludes by discussing the pedagogical and sociocultural impact of this exclusion, particularly on mainstream students’ perceptions and marginalized students’ perceptions of India’s diversity.
Keywords: Textbook analysis; Tribal representation; Marginalized; Tamil Nadu state board; CBSE curriculum